2016
DOI: 10.3727/152599516x14745497664433
|View full text |Cite
|
Sign up to set email alerts
|

Critical Incidents, Emotions, and Value-Added Moments: The London 2012 Spectator Experience

Abstract: In an increasingly complex and demanding sport event environment, spectators expect to fulfill their insatiable hedonistic needs through engaging in memorable customer experiences. However, experience creation and management suffer poor conceptualization and contextualization. Using the case study of London 2012 Olympic spectator experiences and applying a range of mixed-methods tools, this exploratory study advances the emerging research agenda on understanding the nature of critical incidents and accompanyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Research indicates that measures of the consumer experiences must to go beyond an evaluation of primarily cognitive aspects (Bagozzi et al, 1999;Oliver et al, 1997). As suggested by Emery et al (2016), Liu et al (2017) and Wood and Kenyon (2018), this study, therefore, proposes and tests event quality as a measure of consumers' emotional and cognitive experiences in order to understand consumer experiences more holistically. The emotional aspects: immersion, fun and hedonic aspects are integrated into an existing measure of service quality representing a cognitive evaluation of the experience as suggested by Armbrecht (2020).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Research indicates that measures of the consumer experiences must to go beyond an evaluation of primarily cognitive aspects (Bagozzi et al, 1999;Oliver et al, 1997). As suggested by Emery et al (2016), Liu et al (2017) and Wood and Kenyon (2018), this study, therefore, proposes and tests event quality as a measure of consumers' emotional and cognitive experiences in order to understand consumer experiences more holistically. The emotional aspects: immersion, fun and hedonic aspects are integrated into an existing measure of service quality representing a cognitive evaluation of the experience as suggested by Armbrecht (2020).…”
Section: Discussionmentioning
confidence: 95%
“…This perspective is derived from earlier research suggesting that participants attend events for escape, novelty and uniqueness, family and socialisation purposes (Crompton & McKay, 1997;Nicholson & Pearce, 2001;Uysal et al, 1993). These findings indicate that measuring consumer experiences must move beyond an evaluation of cognitive aspects (such as service quality) (Bagozzi et al, 1999;Oliver et al, 1997), and include affective aspects (Emery et al, 2016;Liu et al, 2017;Wood & Kenyon, 2018). Lee et al (2008) show how positive and negative emotions mediate the relationship between cognition and experiential outcomes in a festival context.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Among the shared emotions for a day-long music event were happiness and excitement. Emery et al (2016) also found that emotions experienced during memorable moments at the 2012 Olympics were shared, particularly activating emotions, such as excitement.…”
Section: Anticipation and Emotionsmentioning
confidence: 87%
“…One participant linked post-event satisfaction to the build-up of anticipation of the event over the day; another mentioned excitement that endured. Emery et al (2016) found that pride and especially excitement, both positive-activating emotions, occurred before and during the 2012 Olympic events. Anticipation and excitement began in a "building a moment" phasesometimes years (at the announcement of the London locale), months (at ticket purchase), weeks (via media) and/or days (with the torch relay) before event attendance.…”
Section: Anticipation and Emotionsmentioning
confidence: 98%
“…Event Management has published a growing number of articles related to events and cities. For example, there have been a number of recent studies considering the effects of the Olympic Games in different cities (Emery, Kerr, & Crabtree, 2016;Fairley, Gardiner, & Filo, 2016;Potwarka, Tepylo, Fortune, & Mair, 2016). Other events such as the ECOC have also been analyzed in their urban context (Vareiro, Santos, Remoaldo, & Ribeiro, 2016).…”
mentioning
confidence: 99%